Corporate Governance Attributes and Financial Performance of Quoted Deposit Money Banks in Nigeria - Timothy Aondona Aondover; Kayode Oluwafemi Ishola; Okonkwo Doris Ngozi (Britain International for Academic Research (BIAR) Publisher, 2026)
This study examined the relationship between corporate governance attributes and the financial performance of quoted Deposit Money Banks in Nigeria. The study was motivated by the growing importance of effective corporate governance in enhancing transparency, accountability, investor confidence, and the overall stability of the banking sector. Specifically, the study reviewed key corporate governance mechanisms, including audit committee effectiveness, board meetings, and board independence, and their influence on financial performance indicators such as Return on Assets (ROA), Earnings per Share (EPS), Return on Capital Employed (ROCE), and Total Assets. The study adopted a qualitative research design using the secondary method of data collection. Data were obtained from relevant textbooks, peer-reviewed journal articles, regulatory publications, and other credible online sources. The study was anchored on Agency Theory, which explains the role of corporate governance mechanisms in reducing agency conflicts between shareholders and management while promoting effective monitoring and accountability. Findings from the reviewed literature revealed that corporate governance attributes significantly influence the financial performance of quoted Deposit Money Banks, although the effects vary across different governance mechanisms and performance measures. Board independence was found to positively enhance profitability and capital efficiency, while frequent board meetings may produce mixed outcomes depending on organizational circumstances. The study further revealed that firm size moderates the relationship between corporate governance and financial performance, suggesting that governance structures are more effective when aligned with the operational characteristics of individual banks. The study concludes that corporate governance remains a fundamental driver of accountability, transparency, and financial sustainability in the Nigerian banking sector. It therefore recommends that quoted Deposit Money Banks should strengthen board independence, improve the effectiveness of audit committees, ensure optimal frequency of board meetings, and continuously align governance practices with regulatory requirements and international best practices to enhance financial performance and long-term organizational sustainability.